Some Thoughts on Greetings in English and Arabic (Journal of the College of Education for Women, 2019)
The present study examines the main points of differences in the subject of greetings between the English language and the Arabic language. From the review of the related literature on greetings in both languages, it is found that Arabic greeting formulas are more elaborate than the English greetings, because of the differences in the social customs and the Arabic traditions and the Arabic culture. It is also found that Arabic greetings carry a religious meaning basing on the Islamic principle of “the same or more so”, which might lead to untranslatable loopholes when rendered in English.